2020
DOI: 10.1080/22221751.2020.1812435
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Toxoplasma gondii infection in human cerebral organoids

Abstract: Pluripotent stem cell-derived cerebral organoids have the potential to recapitulate the pathophysiology of in vivo human brain tissue, constituting a valuable resource for modelling brain disorders, including infectious diseases. Toxoplasma gondii, an intracellular protozoan parasite, infects most warm-blooded animals, including humans, causing toxoplasmosis. In immunodeficient patients and pregnant women, infection often results in severe central nervous system disease and fetal miscarriage. However, understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
(52 reference statements)
0
24
0
1
Order By: Relevance
“…To overcome this challenge, efforts are being made to develop co-cultures of GI organoids with immune cells and/or enteric neurons [ 46 , 47 ]. Brain organoids have also been used to study neuro-immune, neuro-endocrine [ 48 ] and host–microbe interactions, including Zika virus, [ 49–51 ] Toxoplasma gondii , [ 52 ] congenital human cytomegalovirus (HCMV) [ 53 ] and Japanese encephalitis virus (JEV) [ 54 ]. Advances in (patient) iPSC-derived GI, ENS and brain organoids with vagal nerve neurons, as well as in methods to co-culture these components, could provide in the future a means to model the gut-brain connection and study the role of microbiota in various aspects of human health and disease [ 48 ].…”
Section: Advanced Tools For Modelling the Human Microbiome-gut-brain mentioning
confidence: 99%
“…To overcome this challenge, efforts are being made to develop co-cultures of GI organoids with immune cells and/or enteric neurons [ 46 , 47 ]. Brain organoids have also been used to study neuro-immune, neuro-endocrine [ 48 ] and host–microbe interactions, including Zika virus, [ 49–51 ] Toxoplasma gondii , [ 52 ] congenital human cytomegalovirus (HCMV) [ 53 ] and Japanese encephalitis virus (JEV) [ 54 ]. Advances in (patient) iPSC-derived GI, ENS and brain organoids with vagal nerve neurons, as well as in methods to co-culture these components, could provide in the future a means to model the gut-brain connection and study the role of microbiota in various aspects of human health and disease [ 48 ].…”
Section: Advanced Tools For Modelling the Human Microbiome-gut-brain mentioning
confidence: 99%
“… 149 , 215 , 216 Toxoplasmosa gondii (TG), an intracellular protozoan parasite with no vaccine or effective treatment, can cause several CNS diseases and neurodevelopmental defects such as mental retardation, seizures, and microcephalus. 150 , 217 , 218 The unusual asexual life cycle of TG, which alternates between tissue cyst-forming bradyzoites and inflammation-inducing tachyzoites, requires a heterogeneous cell population for replication that has had underwhelming results in 2D cultures. 150 , 218 220 Cerebral organoids were able to stimulate the complex TG asexual life cycle, including parasitophorous vacuoles that form cysts, and revealed that TG preferentially infects neuronal cells, astrocytes, and oligodendrocytes and primarily evokes an immune response from IFN-1.…”
Section: Brain Organoid Models For Covid-19 and Infectious Diseasesmentioning
confidence: 99%
“… 150 , 218 220 Cerebral organoids were able to stimulate the complex TG asexual life cycle, including parasitophorous vacuoles that form cysts, and revealed that TG preferentially infects neuronal cells, astrocytes, and oligodendrocytes and primarily evokes an immune response from IFN-1. 150 …”
Section: Brain Organoid Models For Covid-19 and Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This cell line was differentiated into neuronal cells as confirmed by expression of neuronal markers, which were efficiently infected by tachyzoites and supported their replication and development of the cyst stage. A more in-depth understanding of the most inaccessible site of T. gondii infection was achieved by generating brain organoids from the hESC line H9 [ 75 ]. The correct structure and cell types were verified by staining for specific markers, identifying neurones, glia, astrocytes, oligodendrocytes by day 55 of differentiation.…”
Section: Simulation Of Tissue Environment: Organoidsmentioning
confidence: 99%